Electrochemical CO stripping on nanosized Pt surfaces in acid media: A review on the issue of peak multiplicity - Ciapina, Eduardo G. [UNESP]; Santos, Sydney F.; Gonzalez, Ernesto R. (My University, 2018)
This manuscript reviews the complex behavior of the electrochemical oxidation of adsorbed CO (CO stripping) on Pt nanoparticles in acid media. While on low-index Pt single crystals the so-called CO stripping generally exhibits a single, narrow, and well-defined oxidation peak, its oxidation on Pt nanoparticles may produce multiple peaks instead, whose origin is still not fully understood. The issue of peak multiplicity is reviewed based on published articles in the field of electrocatalysis and also on new experimental results. The aim of the present contribution is to highlight the extreme sensitivity of this reaction with respect the state of the surface, microstructure and discuss some other important related features, including the role played by the experimental protocol itself. The influence of the index of crystallografic planes exposed to the electrolyte, particle size, particle agglomeration, CO surface diffusion, adsorbed anions, catalyst support, among other factors on the CO electro-oxidation are presented and discussed. In turn, the ideas presented herein would help scientists to avoid misinterpretation of the experimental results, better design experimental procedures and thus advance in the required knowledge for tuning the Pt nanoparticles to fulfill the requirements for specific applications, such as fuel cell catalysts resistant to CO poisoning.
Keywords: CO oxidation; CO stripping; Electrocatalysis; Electrocatalysts; Nanoparticle; Particle size; Peak multiplicity; Platinum